Values ​​training in the construction of a quality university education. Proposal - Rodríguez Garza, Mayela del Refugio; Sanmiguel Salazar, Francisca (Avances en Supervisión Educativa, 2012)
This paper is a proposal about how to form values in the higher education schools. This proposal was born from an identified need in the process of institutional self-evaluation and feedback over the past years from the national medical education organizations and accrediting agencies, as well as in workshops on curriculum reform that annually are carried out at national level in different parts of the country.Training to values has as aim, the development of the person, such as building a society respectful, democratic and humanizing. Education reform means profound changes and a series of substantial disruptions to current understandings of education and its delivery. It shares the approach advocated by several educators and scholars in recent times as Gimeno Sacristán, Serafin Antúnez, Justa Ezpeleta, in the sense that to achieve this, the center of gravity of the educational system has to be the school, and the school´s, the students. The ultimate goal of education systems and schools is to achieve quality learning and university education because they are those that link learning with the mission, vision, and the kind of students who wish to graduate.Ethical codes and ethics of various professions are the result of rules and criteria by which professionals have tried to regulate their practice, are the set of obligations that must be met in the exercise of the profession.The public higher education institutions, consisten with the philosophy of the universities to which they belong, should graduate professionals committed to meeting the needs of individual and collective health of society to function efficiently in the public and private health system for Mexican people. The next section is a theoretical framework to give a rationale for the proposal, comprehensive conceptualization main ideas of authors, likewise we propose and undertake. Finally the last section is formed by the proposal itself.
Keywords: quality in higher education; higher education comprehensive; professional development in higher education